Impact of Rising Summer Temperatures on Government Sector Tertiary Care Emergency Centers: Addressing Heatstroke and Associated Death Rates in Karachi, Pakistan - Muddassir Syed Saleem; Syeda Zehra Fatima; Hamza Kamran; Ayesha Nouman; Khadija Bibi (SAGE Publishing, 2024)
Rising summer temperatures pose significant challenges to healthcare systems, particularly in low-resource settings. This article examines the impact of heatwaves on government sector tertiary care emergency centers in Karachi, Pakistan and addresses the alarming increases in heatstroke cases and associated mortality during extreme heat events. The study signifies the urgent need for adaptive measures to enhance emergency preparedness, public awareness, and heat mitigation strategies. Addressing heat-related illnesses requires collaborative efforts from healthcare providers, policymakers, and community leaders. Effective interventions can mitigate the impact of rising temperatures on vulnerable populations and reduce heat-associated mortality.